Development of an extruded system with enhanced content of alpha-linolenic polyunsaturated fatty acid - Bochkarev, Sergiy; Chaika, Tetiana; Stankevych, Serhii; Zabrodina, Inna; Balandina, Iryna; Obolentseva, Larysa; Cheremska, Tetiana; Bakirov, Myushfik; Kolontaievskyi, Oleg; Voronov, Roman (Technology center PC, 2024)
The object of the study is the dependence of the technological indicators of the extruded system with an increased ALA content on the composition of the raw materials. The problem of the study is the need to increase the oxidative stability of the lipid component of extrudates, preserve their nutritional value and improve technological characteristics (in particular, porosity). An extruded system with an increased content of alpha-linolenic polyunsaturated fatty acid (ALA) based on a mixture of barley groats and flax seeds has been developed. The influence of flaxseed content on the technological parameters of model extruded systems, in particular porosity and oxidative stability of the lipid component, was studied. It was found that the rational content of flax seeds in the extrusion mixture is 7.0 %, providing the necessary porosity (80 %) and the induction period of accelerated oxidation at a temperature of 80 °C (10 hours). The proposed technological approach makes it possible to increase the shelf life of products while preserving nutritional value. The developed extruded system is promising for further implementation in the food industry, which will contribute to expanding the range of extruded products and increasing their market competitiveness. The effect of antioxidants – ascorbic and ferulic acids on the oxidative stability of lipids of the extruded system was studied: the content of ascorbic acid – 0.06...0.09 %, the content of ferulic acid – 0.10...0.15 %. The lipid component of the extruded system of the developed composition demonstrates a high level of oxidative stability (oxidation induction period – up to 22 hours). The obtained results indicate the possibility of using extruded systems with an increased ALA content to create specialized products with extended shelf life and reduced raw material costs.
Keywords: extruded system; alpha-linolenic acid; flax seeds; barley groats; technological indicators